Analysis of Human Resource Development Through Technical Guidance in Improving Employee Performance - Gulo, Yemina Kristina; Waruwu, Meiman Hidayat; Mendrofa, Syah Abadi; Zega, Yamolala (Jurnal Ilmiah Ekotrans & Erudisi, 2025)
This study analyzes human resource development through Technical Guidance (Bimtek) in improving the performance of Non-Civil Servant Government Employees (PPNPN) at the General Election Commission (KPU) of Nias Regency. The focus of the study is directed at three main objectives, namely: (1) to determine the state of human resource skills at the General Election Commission of Nias Regency, (2) to determine the realization of the technical guidance program that has been attended by employees of the General Election Commission of Nias Regency, (3) to determine the obstacles faced by employees in participating in the technical guidance for employees of the General Election Commission of Nias Regency. The research method employed is a descriptive qualitative approach, utilizing data collection techniques that include interviews, observations, and documentation. The study's results indicate that the condition of human resources has improved, particularly in terms of skills. The implementation of the technical guidance program is considered highly effective in enhancing the performance, skills, and knowledge of PPNPN. Budget limitations for the number of participants, as well as the need for in-depth material and extension of the implementation time. This study concludes that the development of human resources through technical guidance can help employees enhance their skills and knowledge, ultimately achieving individual and agency goals.